Peanut Crackers Substituted with Arrowroot Flour: Physical Properties and Sensory Quality - Sa'diyah, Halimatus; Mariani, Mariani; Sachrom, Sachriani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of arrowroot flour (Maranta arundinacea L.) substitution on the physical properties and sensory quality of peanut rempeyek. The research was conducted at the Food Processing Laboratory, Culinary Education Study Program, Universitas Negeri Jakarta, from April 2025 to October 2025. The method used in this study was an experimental method. The research samples were peanut rempeyek with arrowroot flour substitution at levels of 20%, 35%, and 50%. The physical test included oil absorption measurement using oil paper, carried out in three replications for each sample. The hypothesis testing for physical properties was analyzed using ANOVA followed by Duncan’s test. The results showed that arrowroot flour substitution at 20%, 35%, and 50% significantly affected oil absorption, with the lowest oil absorption found in the 50% substitution treatment. The sensory evaluation was conducted with 45 semi-trained panelists. Based on the Kruskal-Wallis test, the results indicated that arrowroot flour substitution at 20%, 35%, and 50% did not significantly affect the sensory attributes of peanut rempeyek across all evaluated aspects. Sensory quality assessment revealed that all three products had comparable quality. The conclusion of this study is that the 50% substitution sample was the best treatment in terms of oil absorption. Therefore, peanut rempeyek with 50% arrowroot flour substitution is recommended to optimize the utilization of arrowroot flour as an alternative to rice flour.